Strand 4: Adult Learners and New Technology: Study Skills and Personal Development Through Multi-Media Mode - Ward, Jill (Proceedings of the International Conference on Networked Learning, 1998)
This paper describes and critically evaluates the development and delivery of modules written for use through CDRom with the additional use of video material. The modules arc in Study Skills and Personal Development, and are designed for adult learners. The modules were originally offered as a taught course and it is the transposing of these into an alternative mode of delivery which is the focus of the paper. The way in which this potentially widens participation and encourages inclusive learning is explored; as well as the problems of achieving the learning objectives of the modules through computer based learning. A supportive infrastructure is essential if independent learning is to be achieved and the framework for this is described. The problems confronting marginalized learners are recognised and addressed and broader institutional issues raised. The rapid technological changes which have occurred since the inception of the project are also recognised, and as a result of this current developments arc described which will further enhance the learners' experience. Finally, the extension of the project into a European dimension is briefly described.